Frontispiece: New Dual Fluorescent Probe for Simultaneous Biothiol and Phosphate Bioimaging. Issue 42 (12th October 2015) - Resa, Sandra; Orte, Angel; Miguel, Delia; Paredes, Jose M.; Puente‐Muñoz, Virginia; Salto, Rafael; Giron, Maria D.; Ruedas‐Rama, Maria J.; Cuerva, Juan M.; Alvarez‐Pez, Jose M.; Crovetto, Luis
<x xml:space="preserve">Abstract</x> Bioimaging The combined action of inorganic phosphate and glutathione has a clear biological relevance, that is, in cancer, obesity, diabetes, and hypoxia. A new sulfinyl xanthene derivative (DNBS‐GG; DNBS=2, 4‐dinitrobenzenesulfinate, GG=Granada Green) that can act as a simultaneous dual sensor of biological biothiols and phosphate anions was designed, synthesized, and used in cells. Its sensing mechanism implies thiolysis of the sulfinyl group of the weakly fluorescent DNBS‐GG by biological thiols at physiological pH, releasing the fluorescent GG moiety that simultaneously responds to phosphate anions through its fluorescence decay time. For more details see the Full paper by J. M. Cuerva, L. Crovetto et al. on page 14772 ff.